Bio‐Inspired Deaminative Hydroxylation of Aminoheterocycles and Electron‐Deficient Anilines. (7th December 2022) - Ghiazza, Clément; Wagner, Lucas; Fernández, Sergio; Leutzsch, Markus; Cornella, Josep
Abstract: Among the tools available to chemists for drug design of bioactive compounds, the bioisosteric replacement of atoms or groups of atoms is the cornerstone of modern strategies. Despite the undeniable interest in amino‐to‐hydroxyl interchange, enzymatic deaminative hydroxylation remains unmatched. Herein, we report a user friendly and safe procedure to selectively convert aminoheterocycles to their hydroxylated analogues by means of a simple pyrylium tetrafluoroborate salt. The hydroxylation step relies on a Lossen‐type rearrangement under mild conditions thus avoiding the use of strong hydroxide bases. In addition to biorelevant heterocycles, the deaminative hydroxylation of electron‐deficient anilines was also demonstrated. Finally, mechanistic experiments allowed the identification of the key intermediates, thus unveiling a rather unusual mechanism for this formal aromatic substitution. Abstract : Herein, we report a user friendly, scalable and safe procedure to convert aminoheterocycles to their hydroxylated analogues with a pyrylium tetrafluoroborate salt in combination with a hydroxamic acid. The protocol is characterized by a broad functional group tolerance, permitting the selective modification of biorelevant molecules. Mechanistic experiments allowed the identification of key intermediates involved throughout the transformation.